2014
DOI: 10.1089/tmj.2013.0373
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Assessment and Survey of Syrian Refugees' Psychological Stress and Openness to Referral for Telepsychiatry (PASSPORT Study)

Abstract: Women, those who were bilingual, and those with positive HADStress status were less likely to accept telepsychiatry; however, this finding did not reach statistical significance. This study reports a partial acceptance of Syrian refugees for telepsychiatric services despite the high prevalence of psychological stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 9 publications
1
57
0
Order By: Relevance
“…66 The conflict has made delivery of adequate mental health care to these individuals almost impossible, in view of the destruction of infrastructure and violence. A survey of Syrian refugees in Turkey found that nearly half were interested in receiving mental health services through telepsychiatry 67 and, lately, efforts have focused on the use of technology to reach Syrian refugees in Jordan. 68 In view of the elevated burden of untreated mental disorders among refugees, and the long-term consequences on functioning and community participation, efforts are urgently needed to evaluate online cognitive behavioural therapy programmes, SMS text-messaging support, and mobile screening tools for identification of individuals at greatest risk and delivery of effective treatments to refugee populations in diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…66 The conflict has made delivery of adequate mental health care to these individuals almost impossible, in view of the destruction of infrastructure and violence. A survey of Syrian refugees in Turkey found that nearly half were interested in receiving mental health services through telepsychiatry 67 and, lately, efforts have focused on the use of technology to reach Syrian refugees in Jordan. 68 In view of the elevated burden of untreated mental disorders among refugees, and the long-term consequences on functioning and community participation, efforts are urgently needed to evaluate online cognitive behavioural therapy programmes, SMS text-messaging support, and mobile screening tools for identification of individuals at greatest risk and delivery of effective treatments to refugee populations in diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from telemental health pilots with Syrian refugees in Turkey presented at the workshop suggests that scalable interventions for supporting mental health professionals exist, but acceptability of telemental health to patients may be reduced by concerns over security and stigma. 5 Adequate testing of interventions that have shown promise elsewhere (e.g. 'Teaching recovery techniques', an intervention designed to give children affected by war better coping strategies for psychological stress) 13 will be crucial.…”
mentioning
confidence: 99%
“…Participants who screened positive on the PHQ-2 and PHQ-9 were selected for further analysis. PHQ-9 score was categorized into no symptoms (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). PHQ-9 categories and average scores, as well as individual PHQ-9 items were summarized by gender and tested for statistical difference using the Pearson's Chi-Square and the independent t-test.…”
Section: Discussionmentioning
confidence: 99%